1998
DOI: 10.1097/00001756-199806010-00009
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Na+,K+-ATPase from rat brain cortex by propionic acid

Abstract: Buffered propionic acid was injected s.c. into rats twice a day at 8 h intervals from the 6 to 21 days of age. Control rats received saline in the same volumes. The animals were weighed and killed by decapitation at 23 days. Whole brain and cerebral cortex were weighed and synaptic plasma membranes were prepared from cortex for the determination of Na+,K+-ATPase and Mg2+-ATPase activities. Body, whole brain and cortical weights were similar in the two groups, suggesting that propionic acid does not cause malnu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 10 publications
0
20
0
Order By: Relevance
“…Inorganic phosphate production was evaluated by measuring absorbance at 660 nm using malachite green-molybdate dye. The activity was expressed as μM phosphonium ion (Pi) per mg protein per hour [23,24]. Protein concentrations were determined by Coomassie blue staining [25] using bovine serum albumin as a standard.…”
Section: Assay Of Na + K + -Adenosine Triphosphatase Activitymentioning
confidence: 99%
“…Inorganic phosphate production was evaluated by measuring absorbance at 660 nm using malachite green-molybdate dye. The activity was expressed as μM phosphonium ion (Pi) per mg protein per hour [23,24]. Protein concentrations were determined by Coomassie blue staining [25] using bovine serum albumin as a standard.…”
Section: Assay Of Na + K + -Adenosine Triphosphatase Activitymentioning
confidence: 99%
“…PPA possesses many neuropharmacological properties which can account for the short-latency behavioral effects observed in this study. PPA inhibits Na + /K + ATPase [78] and increases NMDA receptor sensitivity [47] which can enhance neural depolarization. This organic acid increases glutamatergic transmission leading to neural hyperexcitability in brain regions linked to locomotor activity.…”
Section: Fig 6: Group Means (±Sem) For (A) Glutathione (Gsh) (B) Glmentioning
confidence: 99%
“…Neurotoxic effects of PA have been also reported but to a lesser extent (Wyse et al 1998;Brusque et al 1999;de Mattos-Dutra et al 2000;Fontella et al 2000;Trindade et al 2002;Rigo et al 2006, Ribas et al 2010a. Thus, it has been observed that PA induces lipid peroxidation and decreases non-enzymatic antioxidant defenses in vitro (Fontella et al 2000) and reduces tissue antioxidant defenses in the hippocampus in vivo .…”
Section: Introductionmentioning
confidence: 97%